Do the means and distributions align with the SJR values of SCImago’s economic subject category lists? - Dobos, Imre; Kovács, Erzsébet; Sasvári, Péter (Public Finance Quarterly, 2025)
Only a few sections of the Hungarian Academy of Sciences (HAS) maintain ranked journal lists, one of which is the IX Section of Economics and Law. The doctoral committees within this section assess candidates for the title Doctor of the Academy of Sciences based on eight lists of ranked international journals. These lists remain unchanged for a fixed period (three to five years). This study examines the extent to which the average SCImago Subject Ranking (SJR) values differ across subject categories within the economic subject areas of the SCImago database To analyze these differences, we apply various models of analysis of variance (ANOVA), including Welch’s ANOVA and the Kruskal-Wallis ANOVA.